GPIHBP1 and the processing of triglyceride-rich lipoproteins - Beigneux, Anne P. (2010)
GPIHBP1 is a new addition to a group of proteins required for the lipolysis of triglyceride-rich lipoproteins. GPIHBP1 contains an acidic domain and an Ly6 domain with ten cysteines. GPIHBP1 binds lipoprotein lipase (LPL) avidly and likely tethers LPL to the luminal surface of capillaries. Inactivation of Gpihbp1 in mice is associated with milky plasma and severe chylomicronemia, even on a low-fat chow diet. Recently, four missense mutations in GPIHBP1 were identified in humans with severe chylomicronemia (C65Y, C65S, C68G, and Q115P). All four mutations involve highly conserved residues within GPIHBP1’s Ly6 domain. This review will provide an update on GPIHBP1’s role in the processing of chylomicrons and the pathogenesis of chylomicronemia.